Causal Discovery Methods to Map the Longitudinal Relationship Between Workplace Microaggressions, Social Support Networks, and Leadership Efficacy in Women - Rodríguez Pérez , Raul; Ortega, Fernanda (Psychology of Woman Journal, 2026)
Objective: The objective of this study is to utilize advanced causal discovery methods on three-wave longitudinal data to precisely map the temporal and structural relationships between workplace microaggressions, the subsequent erosion of social support networks, and the resulting decline in leadership efficacy among professional women. Methods and Materials: This study employed a three-wave longitudinal panel design over a one-year period, collecting data from a sample of 482 professional and managerial women in Mexico. Validated self-report surveys were administered at three distinct time points, each separated by a 6-month interval, to capture the temporal dynamics of the psychological and interpersonal constructs. To transition beyond traditional correlational associations and establish structural directionality, the Peter-Clark (PC) causal discovery algorithm was utilized alongside robust bootstrapping techniques on the R statistical platform, supplemented by formal mediation analysis to quantify indirect pathways. Findings: The causal discovery algorithm successfully identified a robust, fully mediated indirect pathway, eliminating the direct long-term path between early hostilities and later leadership confidence. Specifically, exposure to workplace microaggressions at Time 1significantly eroded social support networks at Time 2, a directed causal edge that was retained in 92.4%of the bootstrap samples. Subsequently, this diminished social support at Time 2directly reduced leadership efficacy at Time 3, a structural path present in 88.7%of the bootstrap samples. Formal mediation analysis confirmed that social support networks act as a significant and critical mediating mechanism in this detrimental dynamic, yielding a standardized indirect effect of -0.046. Conclusion: Subtle workplace hostilities do not merely cause immediate distress, but structurally dismantle the professional social support networks fundamentally required to sustain and cultivate women’s leadership efficacy over time.